Validation of the Arabic Version of Strengths and Difficulties Questionnaire in Early Childhood Education in Qatar - Maha Al-Hendawi (MDPI AG, 2023)
This study examined the validity of the Arabic version of the Strengths and Difficulties Questionnaire (SQD, teacher version) among a sample of young children in Qatar. Teachers rated 502 children aged four to five years from public preschools using the SDQ teacher version. The factor structure of the SDQ was analyzed using exploratory and confirmatory factor analyses. I calculated Cronbach's alpha coefficient and item-total correlations to determine the reliability of the five subscales and overall SDQ. The findings showed acceptable reliability, with the exception of the Peer Problems Scale. Common fit statistics-including the comparative fit index, non-normed fit index, and goodness-of-fit index-were used for the confirmatory factor analysis. In general, satisfactory psychometric characteristics were observed for the preschool SDQ, suggesting that the questionnaire could be administered to preschool-age children in Qatar.